2007
DOI: 10.1016/j.jmb.2007.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Rad54 Oligomers Translocate and Cross-bridge Double-stranded DNA to Stimulate Synapsis

Abstract: Rad54 is a key component of the eukaryotic recombination machinery. Its presence in DNA strand exchange reactions in vitro results in a significant stimulation in the overall reaction rate. Using untagged Rad54, we show that this stimulation can be attributed to enhancement of the formation of a key reaction intermediate known as DNA networks. Using a novel, single DNA molecule, dualoptical tweezers approach we show how Rad54 stimulates DNA network formation. We discovered that Rad54 oligomers possess a unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 49 publications
5
41
0
Order By: Relevance
“…These studies found that Rdh54 could translocates at a rate of approximately 80 bp s −1 . The motion was highly heterogeneous and included transient pauses and translocation direction reversals, in agreement with similar studies on Rad54 7,57. In addition, DNA loop release events were observed occasionally.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These studies found that Rdh54 could translocates at a rate of approximately 80 bp s −1 . The motion was highly heterogeneous and included transient pauses and translocation direction reversals, in agreement with similar studies on Rad54 7,57. In addition, DNA loop release events were observed occasionally.…”
Section: Discussionsupporting
confidence: 88%
“…Single molecule assays of various functions of the recombinase RecA and the eukaryotic homolog Rad51 are presented in Sections 2.2 and 2.3 5,45-56. Observation of the eukaryotic Rad54 and Rdh54 translocation and DNA remodeling activity is discussed in Section 2.4 6,7,57,58. Finally, Section 2.5 summarizes experiments on the HJ specific motor complex RuvAB 59-62…”
Section: Discussionmentioning
confidence: 99%
“…Reactions were initiated by adding Dmc1 or Rad51 to the ssDNA and incubating the sample for 15 min, followed by incubation with Hop2-Mnd1 (5 min) and dsDNA (10 min). Reaction processing was performed as described previously (23) (Fig. 1 A).…”
Section: Coaggregate Assaymentioning
confidence: 99%
“…Rad54 can displace Rad51 protein from dsDNA, reposition nucleosomes, and stimulate DNA strand exchange. Recent single-molecule studies have peered into the behavior of both of these two motor proteins [23-26]. …”
Section: Mechanistic Insights Into Enzyme Function From Single-molecumentioning
confidence: 99%